Construction of Geotourism and Its Contribution to the Sustainability of Regional Development in Australia - KIKUCHI, Toshio; ARIMA, Takayuki (Chigaku zasshi, 2011)
Although there is only one geopark in Australia, there are many geosites and associated clusters. These geosites form the base of geotourism in Australian national and provincial parks and in nature conservation areas. According to the geosites' geographical range and the networks they generate, Australian geotourism can be divided into three types: small-scale, medium-scale, and large-scale geotourism.  Small-scale geotourism is characterized by the local distribution of geosites and of the networks they form. In the Willandra Lakes Region, for example, the regional development of geotourism is limited to a local cluster of geosites and their immediate surroundings. At such a local scale, geotourism does not contribute much to the sustainability of regional development because the relationship between geosites and other regional resources is not strong and does not generate organic networks. This type of geotourism is similar to ecotourism, and the linkage with eco-sites and conservation is important. Medium-scale geotourism is characterized by a broader regional distribution and occurs in combination with a small number of national and provincial parks, and with nature conservation areas such as the Greater Blue Mountain Region. Although geosites and their clusters are linked with some other kinds of regional resource in this type of geotourism, they remain dominated by bio-resources and the natural landscape. This type of geotourism generally complements mass-tourism in areas that are easily accessible from urban areas. On the other hand, large-scale geotourism is characterized by its broader spread and a wider network of geosites such as the Kanawinka Region, where the geopark is located, stretching over large areas of Victoria and South Australia Provinces. In spite of the dispersion of geosites, the relationships among them are strong and the linkage with additional regional resources contributes to the development of geotourism. Therefore, this type of geotourism makes an important contribution to the sustainability of regional development because the relationships among geosites and other regional resources generate multi-functional networks, and thus offers a diversity of tourism options.